N = 2 Chern-Simons-matter theories without vortices - Russo, Jorge G. (2017)
We study N = 2 Chern-Simons-matter theories with gauge group Uk1(1)×Uk2(1). We find that, when k1 + k2 = 0, the partition function computed by localization dramatically simplifies and collapses to a single term. We show that the same condition prevents the theory from having supersymmetric vortex configurations. The theories include mass-deformed ABJM theory with U(1)k× U−k(1) gauge group as a particular case. Similar features are shared by a class of CS-matter theories with gauge group Uk1(1)×⋯×UkN(1).